Comparative genomics provides insights into the potential biocontrol mechanism of two Lysobacter enzymogenes strains with distinct antagonistic activities - Xu, Shuai; Zhang, Ziyu; Xie, Xuewen; Shi, Yanxia; Chai, Ali; Fan, Tengfei; Li, Baoju; Li, Lei (Frontiers in Microbiology, 2022)
Lysobacter enzymogenes has been applied as an abundant beneficial microorganism to control plant disease; however, most L. enzymogenes strains have been mainly reported to control fungal diseases, not bacterial diseases. In this study, two L. enzymogenes strains were characterized, of which CX03 displayed a broad spectrum of antagonistic activities toward multiple bacteria, while CX06 exhibited a broad spectrum of antagonistic activities toward diverse fungi and oomycte, and the whole genomes of the two strains were sequenced and compared. The genome annotation showed that the CX03 genome comprised a 5,947,018 bp circular chromosome, while strain CX06 comprised a circular 6,206,196 bp chromosome. Phylogenetic analysis revealed that CX03 had a closer genetic relationship with L. enzymogenes ATCC29487T and M497-1, while CX06 was highly similar to L. enzymogenes C3. Functional gene annotation analyses of the two L. enzymogenes strains showed that many genes or gene clusters associated with the biosynthesis of different secondary metabolites were found in strains CX03 and CX06, which may be responsible for the different antagonistic activities against diverse plant pathogens. Moreover, comparative genomic analysis revealed the difference in bacterial secretory systems between L. enzymogenes strains CX03 and CX06. In addition, numerous conserved genes related to siderophore biosynthesis, quorum sensing, two-component systems, flagellar biosynthesis and chemotaxis were also identified in the genomes of strains CX03 and CX06. Most reported L. enzymogenes strains were proven mainly to suppress fungi, while CX03 exhibited direct inhibitory activities toward plant bacterial pathogens and showed an obvious role in managing bacterial disease. This study provides a novel understanding of the biocontrol mechanisms of L. enzymogenes, and reveals great potential for its application in plant disease control.